An azobenzene-based photochromic liquid crystalline amphiphile for a remote-controllable light shutter. Issue 55 (12th June 2015) - Kim, Dae-Yoon; Lee, Sang-A; Kim, Huisu; Min Kim, Soo; Kim, Namil; Jeong, Kwang-Un
Abstract : By considering intramolecular conformations and intermolecular interactions, a photochromic liquid crystalline amphiphile is synthesized for a remote-controllable light shutter. Abstract : By considering intramolecular conformations and intermolecular interactions, an azobenzene-based photochromic liquid crystalline amphiphile is synthesized for demonstrating a remote-controllable light shutter by the photo-induced isothermal phase transition between the highly ordered crystal phase and the isotropic liquid phase.